(untitled) (One Health & Risk Management, 2021)
Introduction. The interest in Global Health (HG) as an academic discipline has increased in the last decade. The Rouen School of Medicine is one of the first to offer a GH curriculum in France. The objective was to identify the characteristics and profile of students involved in a GH curriculum. Material and methods. In 2016 and 2017, a cross-sectional study was conducted, including enrolled in the GH course: 3rd and 4th year in medicine, midwifes studies and pharmacy. Based on self-questionnaire, data collected were motivations for health studies, investment in humanitarian associations, opinions about the GH topics. Results. A total of 422 students were included; 122 students attended to GH cursus (GH+) and 300 in control group (GH-). The students of the GH+ group were more likely to get involved in a humanitarian association (22.3% versus 6.7%, p<0.001) and to have already taken part in a humanitarian action (20.5% vs 9.3%, p=0.002). GH+ students were more likely to engage in professional practice abroad or in humanitarian medicine (67% versus 38%, p=0.001). Work in vulnerable populations, the impacts of climate change on health are frequent topics in GH+ group.Conclusions. Students enrolled in GH cursus presented a particular profile: predominantly female, open to The World, involved in caritative associations and aware of the importance of interculturality in the care relationship. Integrated training of future health workers is a promising avenue for a better management of effect of sanitary crisis (i.e. pandemic, climate change and health effects, etc.).